Influence of Functional Groups on the Ene Reaction of Singlet Oxygen with 1, 4‐Cyclohexadienes. (11th May 2021) - Fudickar, Werner; Metz, Melanie; Mai‐Linde, Yasemin; Krüger, Tobias; Kelling, Alexandra; Sperlich, Eric; Linker, Torsten
Abstract: The photooxygenation of 1, 4‐cyclohexadienes has been studied with a special focus on regio‐ and stereoselectivities. In all examples, only the methyl‐substituted double bond undergoes an ene reaction with singlet oxygen, to afford hydroperoxides in moderate to good yields. We explain the high regioselectivities by a "large‐group effect" of the adjacent quaternary stereocenter. Nitriles decrease the reactivity of singlet oxygen, presumably by quenching, but can stabilize proposed per‐epoxide intermediates by polar interactions resulting in different stereoselectivities. Spiro lactams and lactones show an interesting effect on regio‐ and stereoselectivities of the ene reactions. Thus, singlet oxygen attacks the double bond preferentially anti to the carbonyl group, affording only one regioisomeric hydroperoxide. If the reaction occurs from the opposite face, the other regioisomer is exclusively formed by severe electrostatic repulsion in a perepoxide intermediate. We explain this unusual behavior by the fixed geometry of spiro compounds and call it a "spiro effect" in singlet oxygen ene reactions. Abstract : Unsaturated spiro compounds react with singlet oxygen to hydroperoxides with high site‐, regio‐ and stereoselectivities. The preferential attack occurs anti to the carbonyl group and the "green" methyl group undergoes the ene reaction, whereas the "blue" methyl group reacts exclusively during syn attack. We explain this behavior by perepoxide intermediates and the fixed geometry of 1, 4‐cyclohexadienes, resulting in a new "spiro effect" in singlet oxygen ene reactions.